2022
DOI: 10.1039/d2cy00583b
|View full text |Cite
|
Sign up to set email alerts
|

Nickel selenide as an efficient electrocatalyst for selective reduction of carbon dioxide to carbon-rich products

Abstract: Identifying new catalyst composition for carbon dioxide electroreduction to high value products has been at the center of attraction over the last several years. In this article, nickel selenide, NiSe2...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 47 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…The electronic state and steric configuration of the active center in the catalyst can determine the type of intermediates produced and the adsorption energies in possible competing reactions; thus, they have been regarded as the keys to promoting acetic acid yields. For instance, NiSe 2 has been reported as an efficient electrocatalyst due to its stabilizing effect on *CO intermediate, leading to the formation of acetic acid, 81 while some amount of C 2 by‐product, ethanol, is also produced. Recently, different Cu‐containing catalysts such as Mo 8 @Cu/titannium dioxide nanotube arrays, meso‐tetra(4‐carboxyphenyl)porphyrinic/Cu(OH) 2 and conducting COF with Cu isolated sites are proven as excellent catalysts 144–146 .…”
Section: Fundamentals Of Catalyzing Co2 Into Carboxylic Acidmentioning
confidence: 99%
“…The electronic state and steric configuration of the active center in the catalyst can determine the type of intermediates produced and the adsorption energies in possible competing reactions; thus, they have been regarded as the keys to promoting acetic acid yields. For instance, NiSe 2 has been reported as an efficient electrocatalyst due to its stabilizing effect on *CO intermediate, leading to the formation of acetic acid, 81 while some amount of C 2 by‐product, ethanol, is also produced. Recently, different Cu‐containing catalysts such as Mo 8 @Cu/titannium dioxide nanotube arrays, meso‐tetra(4‐carboxyphenyl)porphyrinic/Cu(OH) 2 and conducting COF with Cu isolated sites are proven as excellent catalysts 144–146 .…”
Section: Fundamentals Of Catalyzing Co2 Into Carboxylic Acidmentioning
confidence: 99%
“…Recently, Saxena et al reported copper selenide [49] and cobalt telluride [50] that are able to reduce CO 2 to C2 products, such as acetic acid, with greater than 80% Faradaic efficiency (FE) and 75% selectivity at a low applied potential. In a nickel selenide electrocatalyst system, the selectivity of the product can be controlled by the applied potential, and an FE of over 98% can be achieved for acetic acid at lower applied potential [51]. By fine tuning the CO intermediate adsorption energy on the active site using a bimetal copper cobalt selenide electrocatalyst, an FE of 100% towards C2 products such as ethanol and acetic acid was achieved [52].…”
Section: Comparisons Of Biocatalysts With Electrocatalysts For Co 2 R...mentioning
confidence: 99%
“…Recently, there has been an increase in the application of transition-metal chalcogenides as electrocatalysts owing to their high electrical conductivity and enriched redox chemistry. , Examples of such transition-metal chalcogenides include molybdenum selenide (MoSe 2 ), iron selenide (FeSe 2 ), nickel selenide (NiS 2 ), bismuth selenide (Bi 2 Se 3 ), and copper selenide (CuSe and Cu 2 Se), which have been used as sensors. ,,, Over the past few years, nickel and other transition-metal-based chalcogenides have been synthesized and explored for various electrochemical and electrocatalytic applications, including batteries, carbon dioxide reduction, oxygen evolution reaction, hydrogen evolution reaction, , as supercapacitors, , and as solar cells. , However, the use of nickel-selenide-based compositions in electrochemical sensors is still rare.…”
Section: Introductionmentioning
confidence: 99%